Balancing Seniority Rewards and Performance: Challenges and Solutions in Human Resource Management - Adelia Azzahra; Septien Dwi Savandha; Mohamad Maulana Ridzki; Amelia Amelia (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
The study examined the impact of reward and compensation systems on employee performance in medium-sized companies, focusing on workers who had been working for a long time but showed declining performance. Through a qualitative case study approach, this study identifies challenges and dynamics in the implementation of seniority and performance-based reward systems. The results show that seniority-based reward systems tend to be less effective because they give significant recognition to existing employees even though their productivity decreases, while new employees who contribute highly are less rewarded accordingly. In contrast, performance-based compensation systems have proven to be more effective in improving the motivation and retention of high-performing employees. However, the main challenge in this system is determining fair and transparent performance metrics. A hybrid approach that combines elements of seniority and performance can create a balance, but it requires special attention to fairness and consistency in its implementation. The study's main recommendations are the development of a fair and transparent reward system, continuous evaluation, and employee involvement in developing and reviewing the reward system to increase motivation and acceptance. This research makes an important contribution to a more effective and sustainable human resource management strategy.